Three new species of Anchylorhynchus Schoenherr, 1836 from Colombia (Coleoptera: Curculionidae; Curculioninae; Acalyptini) - de Medeiros, Bruno A.s.; Núñez-Avellaneda, Luis A. (Zootaxa, 2013)
Three new species of the genus Anchylorhynchus from Colombia, are described: Anchylorhynchus pinocchio sp. nov., A. centrosquamatus sp. nov. and A. luteobrunneus sp. nov.. A morphological description, including the male genitalia, is pro-vided for each species as well as a comparison with similar species within the genus. All three species are found in inflo-rescences of species of Syagrus Mart. (Arecaceae). The adults are pollinators and the larvae develop inside fruits and feed on the endosperm, interrupting seed formation and causing fruit abortion.